Personalised cancer medicine future crafting in the genomic era - Kerr, Anne, 1969- (Inscriptions., 2021)
What does it mean to personalise cancer medicine? Drawing on an ethnographic study with cancer patients, carers and practitioners in the UK, this book traces their efforts to access and interpret novel genomic tests, information and treatments as they craft personal and collective futures. Exploring multiple experiences of new diagnostic tests, research programmes and trials, advocacy and experimental therapies, the authors chart the different kinds of care and work involved in efforts to personalise cancer medicine, as well as the ways in which benefits and opportunities are unevenly realised and distributed. Comparing these experiences with policy and professional accounts of the 'big' future of personalised healthcare, the authors show how hope and care are multi-faceted, contingent and, at times, frustrated in the everyday complexities of living and working with cancer.